Three-Year Outcomes Following Mitral Valve-in-Ring and Valve-in-Valve Procedures - Gaekel, Daniel Maldonado; Waldschmidt, Lara; Ludwig, Sebastian; Kalbacher, Daniel; Schirmer, Johannes; Blankenberg, Stefan; Reichenspurner, Hermann; Schofer, Niklas; Schaefer, Andreas (The Thoracic and Cardiovascular Surgeon, 2025)
In patients at elevated risk for redo mitral valve surgery, transcatheter mitral valve replacement (TMVR) can be taken into consideration as a less invasive alternative. However, long-term outcome data on mitral valve-in-ring (ViR) and valve-in-valve (ViV) procedures are scarce. We herein report the 3-year outcomes following these interventions.Between 2014 and 2023, 51 consecutive patients received ViR/ViV TMVR at our center. Baseline, periprocedural, and 3-year outcome parameters were analyzed according to M-VARC criteria.Among 51 patients (70.9 ± 13.6 years, Society of Thoracic Surgeons (STS) score 3.3 ± 2.3%, left ventricular ejection fraction (LVEF) 50 ± 12%), 19 underwent ViR and 32 underwent ViV TMVR. Follow-up ranged from 1 to 71 months. The 30-day mortality rate was 5.9% (3/51 patients). Over time, access shifted from transapical to transseptal (p for trend <0.01). Rehospitalization, neurological events, and myocardial infarction occurred in 2.0% (1/51 patients), 2.0% (1/51 patients), and 0.0% of the cases, respectively. No structural valve failure was observed. Functional failure was 3.9% of cases due to significant residual mitral valve regurgitation (MR). Most paravalvular leak occluder implantations were performed in ViR patients (6/9, 66.7%; four rigid rings and two semirigid rings). Three-year survival was 87.5% for ViR and 83.4% for ViV, with no difference between groups.Mitral ViR and ViV procedures demonstrate acceptable safety and clinical efficacy up to 3 years. Rigid annuloplasty rings are associated with an increased risk of significant residual regurgitation. Over the last decade, a clear transition from the transapical to the transseptal access has been observed, further reducing procedural trauma in this high-risk subset of patients.
Keywords: mitral valve surgery; heart valve surgery; reoperation